Fractional flow reserve or optical coherence tomography guidance to revascularize intermediate coronary stenosis using angioplasty (FORZA) trial: study protocol for a randomized controlled trial - Burzotta, Francesco (BioMed Central, 2014)
BACKGROUND: The management of patients with angiographically intermediate coronary lesions is a major clinical issue. Fractional flow reserve provides validated functional insights while optical coherence tomography provides high resolution anatomic imaging. Both techniques may be applied to guide management in case of angiographically intermediate coronary lesions. Moreover, these techniques may be used to optimize the result of percutaneous coronary intervention. We aim to compare the clinical and economic impact of fractional flow reserve versus optical coherence tomography guidance in patients with angiographically intermediate coronary lesions. METHODS/DESIGN: Patients with at least one angiographically intermediate coronary lesion will be randomized (ratio 1:1) to fractional flow reserve or optical coherence tomography guidance. In the fractional flow reserve arm, percutaneous coronary intervention will be performed if fractional flow reserve value is ≤0.80, and will be conducted with the aim of achieving a post-percutaneous coronary intervention fractional flow reserve target value of ≥0.90. In the optical coherence tomography arm, percutaneous coronary intervention will be performed if percentage of area stenosis (AS%) is ≥75% or 50 to 75% with minimal lumen area <2.5 mm(2), or if a major plaque ulceration is detected. In case of percutaneous coronary intervention, optical coherence tomography will guide the procedure in order to minimize under-expansion, malapposition, and edge dissections. Cost load and clinical outcome will be prospectively assessed at one and thirteen months. The assessed clinical outcome measures will be: major cardiovascular events and occurrence of significant angina defined as a Seattle Angina Questionnaire score <90 in the angina frequency scale. DISCUSSION: The FORZA trial will provide useful guidance for the management of patients with coronary artery disease by prospectively assessing the use of two techniques representing the gold standard for functional and anatomical definition of coronary plaques. TRIAL REGISTRATION: Clinicaltrials.gov NCT01824030